Teaching and Learning of G.C.E (A/L) ‘General English’ at selected schools in Jaffna District: A Survey on Objective, Practice and Attitude of Teachers and Students. - Sivaji, K. (University of Jaffna, 2014)
This research paper probes into the area of teaching and learning of ‘General English’ in G.C.E (A/L) in Jaffna. The varied levels of English Language knowledge that the students gained in G.C.E (A/L) has strong impact on the syllabus designing of ESL (English as a Second Language) and ESP (English for Specific purposes) courses for university entrants. Thus it is significant to investigate this area in order to understand and obtain basic information regarding the English Language proficiency level, attitude and practice of university entrants who are supposed to be identified under UTEL (University Teaching of English Language) bench marks before commencing their English courses at universities. This survey was carried out among the teachers and students of four state schools in Jaffna forming groups of forty students and ten teachers of English. In order to investigate the attitude and practice of both teachers and students, separate questionnaires were administered and the results revealed that though there were positive attitude and strong instrumental motivation towards English language learning, the course objective is not achieved as the practice did not co-relate with the course objective. The limitation of this study is that it is a small scale survey consisting only a group of forty students and ten teachers.
Keywords: attitude; General english; instrumental motivation; objective; practice